Atomic spectrometry update: review of advances in the analysis of clinical and biological materials, foods and beverages. Issue 3 (22nd February 2021) - Patriarca, Marina; Barlow, Nicola; Cross, Alan; Hill, Sarah; Robson, Anna; Taylor, Andrew; Tyson, Julian
Abstract : This review discusses developments in elemental mass spectrometry, atomic absorption, emission and fluorescence, XRF and LIBS, as applied to the analysis of specimens of clinical interest, foods and beverages. Sample preparation procedures and quality assurance are also included. Abstract : This update covers publications from the second half of 2019 to the middle of 2020. Techniques and applications relevant to clinical and biological materials, foods and beverages are discussed in the text, presenting key aspects of the work referenced, while the tables provide a summary of the publications considered. A new table has been introduced to include the large number of sample preparation papers that were seen. Reference intervals for quite specific groups and environmental settings were reported, reflecting focussed concerns rather than large general populations. Technical developments include applications of spICP-MS and ICP-QQQMS, particularly to NPs and elemental speciation. Measuring elements as tags for indirect clinical determinations is featured in this ASU as the number of such papers is gradually increasing. As in previous reviews, work featuring cancer and Alzheimer's disease continues, but obesity, Cu metabolism and absorption of metals through skin are of current interest among the clinical applications of atomic spectroscopy. As meat-avoidance increases in many populations the elemental composition of vegetarian and vegan foods is attracting more attention. A study of As in rice-based infant formulas and foods reported levels above the EU limit in all samples, with much of it as iAs. On a similar theme, concentrations of elements in milk from yak and camel were measured alongside the less exotic species, cow, goat and buffalo. Elemental analysis of wines to discriminate authenticity is regularly included in these updates but this approach is now applied to saffron and coconut sugar, as foods which attract commercial interest.